2021
DOI: 10.1002/uog.23531
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pre‐eclampsia in twin pregnancy by maternal factors and biomarkers at 11–13 weeks' gestation: data from EVENTS trial

Abstract: Objectives First, to validate a previously developed model for screening for pre‐eclampsia (PE) by maternal characteristics and medical history in twin pregnancies; second, to compare the distributions of mean arterial pressure (MAP), uterine artery pulsatility index (UtA‐PI), serum placental growth factor (PlGF) and serum pregnancy‐associated plasma protein‐A (PAPP‐A) in twin pregnancies that delivered with PE to those in singleton pregnancies and to develop new models based on these results; and, third, to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…If cfDNA testing is adopted as a first-line method of screening for trisomy in twin pregnancy, it is still imperative that women should be offered an 11-14-week scan for, first, accurate dating of pregnancy from the crown-rump length of the largest twin, second, diagnosis of chorionicity, which is the main determinant of a wide range of adverse outcomes 34 , third, measurement of fetal nuchal translucency thickness and assessment of intertwin discordance in crown-rump length, which have a strong influence on adverse pregnancy outcome 35,36 , fourth, diagnosis of a vanishing twin, because this would preclude the use of cfDNA testing for at least 16 weeks after the estimated time of fetal demise 37,38 , fifth, early diagnosis of major fetal abnormalities 39 , sixth, to determine the presence of major defects, such as holoprosencephaly or exomphalos, in which case an invasive test with microarray rather than cfDNA testing would be the appropriate pregnancy management 40 , seventh, early screening for preterm pre-eclampsia, which is 8-9-times more common in twins than in singleton pregnancies 41,42 , and, eighth, measurement of cervical length, because, if this is short, prophylactic use of vaginal progesterone could substantially reduce the risk of preterm birth 43 .…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…If cfDNA testing is adopted as a first-line method of screening for trisomy in twin pregnancy, it is still imperative that women should be offered an 11-14-week scan for, first, accurate dating of pregnancy from the crown-rump length of the largest twin, second, diagnosis of chorionicity, which is the main determinant of a wide range of adverse outcomes 34 , third, measurement of fetal nuchal translucency thickness and assessment of intertwin discordance in crown-rump length, which have a strong influence on adverse pregnancy outcome 35,36 , fourth, diagnosis of a vanishing twin, because this would preclude the use of cfDNA testing for at least 16 weeks after the estimated time of fetal demise 37,38 , fifth, early diagnosis of major fetal abnormalities 39 , sixth, to determine the presence of major defects, such as holoprosencephaly or exomphalos, in which case an invasive test with microarray rather than cfDNA testing would be the appropriate pregnancy management 40 , seventh, early screening for preterm pre-eclampsia, which is 8-9-times more common in twins than in singleton pregnancies 41,42 , and, eighth, measurement of cervical length, because, if this is short, prophylactic use of vaginal progesterone could substantially reduce the risk of preterm birth 43 .…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…For pre-eclampsia <37 weeks, the DR was 25% for a 10% FPR. 26 The combination of maternal risk factors, uterine artery Doppler, mean arterial pressure and maternal serum placental growth factor increased the DR to 86% for a 10% FPR for delivery with early-onset preeclampsia <32 weeks' gestation.…”
Section: Key Findings and Recommendations Related To Aspirin Prophylaxismentioning
confidence: 97%
“…For preeclampsia <37 weeks, the DR was 41% for a 10% FPR. 26 The evidence from the ASPRE trial on the effectiveness of low-dose aspirin (150mg/day) in the prevention of preeclampsia relates to singleton pregnancies only, as the trial excluded multiple pregnancies.…”
Section: Key Findings and Recommendations Related To Aspirin Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Twin pregnancies, compared to singletons, are at increased risk of pregnancy complications, including miscarriage, stillbirth, preterm birth, fetal growth restriction, and preeclampsia [10][11][12]. There is contradictory evidence concerning the incidence of GDM in twin pregnancies, with some studies reporting that this is higher than in singletons [13][14][15][16][17][18], while others found that the rates are similar [17,18].…”
Section: Introductionmentioning
confidence: 99%